2011
DOI: 10.3109/01612840.2010.531518
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality and Consumers of Mental Health Services: The Impact of Gender and Boundary Issues

Abstract: The importance of sexuality to humanity is clearly acknowledged. However, for consumers of mental health services, it tends to be a neglected topic. Although nurses are at the forefront of mental health service delivery, evidence suggests they are reluctant to include sexuality as part of their care. This article describes the findings from a qualitative exploratory research project that examined mental health nurses' attitudes to discussing sexuality with consumers. Fourteen mental health nurses from a servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…From here, nurses are given Approval to engage with consumers on the topic. Approval is a vital step in this process (Volman & Landeen, 2007), because of the common barriers related to boundary and gender concerns (Quinn, Happell, & Browne, 2011b). There is a need to provide nurses with permission to talk about this topic (Magnan et al, 2005;McCann, 2010;Odey, 2009;Wright & Pugnaire-Gros, 2010) and to let them know, that consumers are not only willing to engage, but are in a position where they are waiting for nurses to initiate discussion on the topic (Kelly & Conley, 2004;McCann, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…From here, nurses are given Approval to engage with consumers on the topic. Approval is a vital step in this process (Volman & Landeen, 2007), because of the common barriers related to boundary and gender concerns (Quinn, Happell, & Browne, 2011b). There is a need to provide nurses with permission to talk about this topic (Magnan et al, 2005;McCann, 2010;Odey, 2009;Wright & Pugnaire-Gros, 2010) and to let them know, that consumers are not only willing to engage, but are in a position where they are waiting for nurses to initiate discussion on the topic (Kelly & Conley, 2004;McCann, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…2011a) issues with both male and female consumers. Concerns about boundary issues, particularly in relation to female consumers, were previously identified by the participants as a barrier to talking about sexuality (Quinn, Happell, & Browne, 2011). The nurse participants were able to demonstrate support for consumers struggling with sexual identity issues, and were accepting of consumer sexual choices, offering support toward them, and taking advantage of this situation to provide education regarding sexual safety and the importance of receiving sexual health checks.…”
Section: Discussionmentioning
confidence: 99%
“…Consumers have the right to have their sexual concerns addressed in care (Krebs, 2007). Consumers may feel embarrassed and anxious (Cook, 2000; Quinn, Happell, & Browne, 2011) or have fear of being labeled or ridiculed by staff for their interest in sex (McCann, 2010). In fact, consumers report being eager and receptive to discuss these issues (Kelly & Conley, 2004), and welcome the opportunity to discuss their sexual health concerns (McCann, 2000) when nurses are willing to raise the topic (Kelly & Conley, 2004).…”
mentioning
confidence: 99%
“…There are, of course, many reasons why discussing sex and sexuality is a neglected area in the psychiatric consultation. It has been suggested that some mental health professionals feel uncomfortable discussing sex with patients of the opposite gender owing to concerns over professional boundaries being crossed (Quinn 2011). In some cases, professionals are reluctant to discuss the topic because they perceive that it is not their role to talk about sex or they do not feel comfortable dealing with issues that might be raised (Tsai 2004).…”
Section: Learning Objectivesmentioning
confidence: 99%